Respect for Women in Religious Value - Nilufar Djurayeva (Indonesian Journal of Cultural and Community Development, 2019)
In this article, a scientific analysis of the female factor in the history of Uzbek statehood is carried out. Scientifically studied thousands of human history, linked by the leadership of women, the status of women in the ancient history of Central Asia, the exaltation of women in the "Avesta", the proof of the equality of women in Islam.